Cine MRI characterizes HFpEF and HFrEF in post-capillary pulmonary hypertension. Issue 139 (June 2021) - Lin, Kai; Sarnari, Roberto; Pathrose, Ashitha; Gordon, Daniel Z.; Blaisdell, Julie; Markl, Michael; Carr, James C.
Highlights: MRI-derived left ventricular (LV) indices are related with right heart catheterization results in post-capillary pulmonary hypertension (PH). There are significant differences on the levels of multiple LV and RV indices between post-capillary PH caused by HFpEF and HFrEF. There is no difference on the incidence of reactive PH in post-capillary PH caused by HFpEF and HFrEF. Abstract: Purpose: To test the hypothesis that cine MRI can be used to characterize features of left and right ventricles in post-capillary pulmonary hypertension (PH) caused by heart failure (HF) with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF). Methods: With the approval of institution review board (IRB), 28 consecutive post-capillary PH patients (11 males, 62.1 ± 13.4 years old, range 39–89 years old) underwent cine MRI scans. Cine MRI-derived left ventricular (LV) ejection fraction (LVEF) and other function, motion, and deformation indices (acquired with heart deformation analysis [HDA]) were compared between PH-HFpEF (defined as LVEF ≥ 50 %]) and PH-HFrEF (LVEF < 50 %) patients and were related with right ventricular (RV) indices and right heart catheterization (RHC)-derived pulmonary artery measurements. Results: Totally 19 patients (68 %, 95 % confident interval [CI] 49 %–86 %) were assigned to PH-HFpEF group while 9 (32 %) was assigned to the PH-HFrEF group. There were differences of LV and right ventricular (RV) global functional indices, LV mass, LV displacement, velocity, strain and strain rate between the two patient groups. Cine MRI-derived LV indices had broad associations with RV indices and RHC measurements. LVEF was negatively correlated with pulmonary capillary wedge pressure (PCWP) (r = -0.5, p = 0.007). LV cardiac index (LVCI) was associated with systolic pulmonary artery pressure (sPAP) (r = 0.443, p = 0.018). Conclusions: PH-HFpEF and PH-HFrEF patients present dissimilar function, motion and deformation features in LV and RV. Cine MRI-derived LV measures are correlated with hemodynamic abnormalities of PH.